A review of wave mechanics in the pulmonary artery with an emphasis on wave intensity analysis. (29th September 2016) - Su, J.; Hilberg, O.; Howard, L.; Simonsen, U.; Hughes, A. D.
Abstract: Mean pulmonary arterial pressure and pulmonary vascular resistance (PVR) remain the most common haemodynamic measures to evaluate the severity and prognosis of pulmonary hypertension. However, PVR only captures the non‐oscillatory component of the right ventricular hydraulic load and neglects the dynamic compliance of the pulmonary arteries and the contribution of wave transmission. Wave intensity analysis offers an alternative way to assess the pulmonary vasculature in health and disease. Wave speed is a measure of arterial stiffness, and the magnitude and timing of wave reflection provide information on the degree of impedance mismatch between the proximal and distal circulation. Studies in the pulmonary artery have demonstrated distinct differences in arterial wave propagation between individuals with and without pulmonary vascular disease. Notably, greater wave speed and greater wave reflection are observed in patients with pulmonary hypertension and in animal models exposed to hypoxia. Studying wave propagation makes a valuable contribution to the assessment of the arterial system in pulmonary hypertension, and here, we briefly review the current state of knowledge of the methods used to evaluate arterial waves in the pulmonary artery.